Electricity sector in India policy and regulation - Kumar, Alok.; Chatterjee, S. K. (Sushanta Kumar) (New Delhi : Oxford University Press, 2012)
Power shortage may very well be one of the major bottlenecks threatening the economic growth of India. Thus power, and particularly electricity, assumes top priority in maintaining a stable growth rate and ensuring energy security. After almost 10 years since the enactment of the Electricity Act, 2003 (a major landmark in second generation reforms), this book reviews the reform process and undertakes a detailed analysis of electricity policy, regulation, and performance, and comprehensively covers power infrastructure and management in India.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Electric utilities -- India; Energy policy -- India